STATE OF EXCEPTION THROUGH RASISME IN GO SET A WATCHMAN IN AGAMBEN’S POLITICAL PHILOSOPHY - Damay Rahmawati; Ramadhani Ardianto Karsa Sunaryono; Mira Utami (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
This study aims to see racism in the novel Go Set a Watchman by Harper Lee as state of exception; a political philosophy of Agamben. Agamben's idea of ​​state of exception is used in this study as the theoretical framework. This research specifically reveals how racism becomes part of state of exception in American society around 1960s when the novel was written. The analysis focuses on issues of racism in American society as depicted in the novel. The issue of racism is taken with the aim of analyzing state of exception in USA, in dealing with racial discrimination. After analyzing the issues of racism and state of exception in the novel, this study reveals that racism in American society is politically structured. The finding of this study is the discrimination experienced by lower class citizens who are dominated by black people, as the impact of state of exception which affects their citizenship rights.